Gateway to Global Development: Prospect for the Azerbaijani Diaspora - Tsikhonia, Samira; Nabieva, Khaviza; Eyvazzada, Nigar; Aghayev, Anar (ADA University, 2023)
Diaspora and diaspora organizations have become the valuable actor in the conduct of international affairs. Their unique position as connectors between the hostland and homeland provide States with an opportunity to utilize their potential. Effective diaspora engagement can have a positive impact on the social-economic development of the country. The method of engagement with diaspora organizations should be defined based on unique characteristics and individual needs of each diaspora. For this study, the analyzes of Azerbaijan diaspora was chosen for investigation of policies options for diaspora mobilization. The data was gathered by the means of primary and secondary sources. The conceptual framework was developed based on information gathered from local and international sources. The first-hand evidence was produced as a result of three productive interviews with distinguished Azerbaijani figures in the field of diaspora activism. The gathered data was used to lay down the profile of Azerbaijani diaspora community to implement the proposed policies to increase the engagement of diaspora organizations in the socio-economic development of Azerbaijan. Given the relative limits of data and time, more study on diaspora is required to better understand the peculiarities of Azerbaijan diaspora and its impact on socio-economic development.
Keywords: Diaspora -- Azerbaijan; Economic development -- Azerbaijan; Transnationalism -- Social aspects; Public and International Affairs